2009
DOI: 10.1134/s106816200902006x
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide analogues containing internucleotide C3′-CH2-C(O)-NH-C5′ bonds

Abstract: A dinucleoside bearing an amide internucleotide C3'-CH2-C(O)-NH-C5' bond was synthesized by the interaction of 3'-deoxy-3'-carboxylmethylribothymidine-2',3'-lactone obtained by hydrolysis of 2'-O-acetyl-5'-O-benzoyl-3'-deoxy-3'-ethoxycarboxylmethylribothymidine with 5'-deoxy-5'-amino-3'-O-(tert-butyldimethylsilyl)thymidine. After standard manipulations with protective groups, the dinucleoside was converted into 3'-O-(2-cyanoethyl-N,N'-diisopropylphosphoroamidite), which was used for the synthesis of modified o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…This derivative was suitable for introducing thymine, thus affording 39 . Hydrolysis of the iso -butyl sulfonate ester moiety in 39 could be achieved in the presence of the levulinic ester moiety, after which a 5′-amino 3′-TBDMS-protected deoxy-thymidine derivative reacted with PFP-ester 40 and gave sulfonamide-containing dinucleotide derivative 41 . In the final steps, the DMT-protective group was introduced at the 5′-end and the phosphoramidite moiety at the 3′-end, thereby completing the synthesis of sulfonamide-containing dinucleotide 45 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This derivative was suitable for introducing thymine, thus affording 39 . Hydrolysis of the iso -butyl sulfonate ester moiety in 39 could be achieved in the presence of the levulinic ester moiety, after which a 5′-amino 3′-TBDMS-protected deoxy-thymidine derivative reacted with PFP-ester 40 and gave sulfonamide-containing dinucleotide derivative 41 . In the final steps, the DMT-protective group was introduced at the 5′-end and the phosphoramidite moiety at the 3′-end, thereby completing the synthesis of sulfonamide-containing dinucleotide 45 .…”
Section: Resultssupporting
confidence: 93%
“…To a solution of 40 (32 mg, 50 μmol) in DMF (2 mL) was added 5′-amino 3′-TBDMS-protected deoxy-thymidine derivative (37 mg, 100 μmol) and DiPEA (18 μL, 100 μmol). The resulting mixture was heated to 60 °C by microwave irradiation and stirred for 20 min.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Our early studies on amide-modified RNA showed that both AM1 and AM2 linkages having either 2′–OH or 2′- O -methyl neighboring groups (R in Figure ) were well accommodated in A-form RNA duplexes. , AM2 was more stabilizing in RNA duplexes than AM1, whereas in DNA-RNA heteroduplexes, the trend was opposite . Both AM1 and AM2 were destabilizing in DNA duplexes. , Our group pursued detailed thermodynamic and nuclear magnetic resonance (NMR) structural studies that showed that AM1 internucleoside linkages were surprisingly effective mimics of phosphates, causing little, if any, distortion of the structure, change in thermal stability, or difference in hydration of A-form RNA duplexes (Figure ). In another study, we showed that three consecutive AM1 linkages in the middle of a short RNA duplex caused some loss of thermal stability, but only a modest alteration of the structure of the RNA .…”
Section: Historical Perspectivementioning
confidence: 99%
“…17 Both AM1 and AM2 were destabilizing in DNA duplexes. 17,23 Our group pursued detailed thermodynamic and nuclear magnetic resonance (NMR) structural studies that showed that AM1 internucleoside linkages were surprisingly effective mimics of phosphates, causing little, if any, distortion of the structure, change in thermal stability, or difference in hydration of A-form RNA duplexes (Figure 2). 3 In another study, we showed that three consecutive AM1 linkages in the middle of a short RNA duplex caused some loss of thermal stability, but only a modest alteration of the structure of the RNA.…”
Section: ■ Historical Perspectivementioning
confidence: 99%